Middle East and the cold war : between security and development (Cambridge Scholars Pub., 2012)
There have been quite a lot of attempts to find out exactly what the impact of the Cold War on the Middle East was, and this from different disciplinary perspectives. This volumes tries to integrate the historical debate with new fresh insights thanks to.